2015
DOI: 10.1093/heapro/dav050
|View full text |Cite
|
Sign up to set email alerts
|

Home smoking restrictions before, during and after pregnancy—a qualitative study in rural China

Abstract: Worldwide, many nonsmokers (often women and children) are exposed to second-hand smoke (SHS) in home settings, as men retain their traditional power and control within their family and women and children have limited agency to intervene. This study, set up to explore home smoking management in rural China, found that some women were able to positively intervene to restrict men's smoking at three key stages: prior to conception, during their pregnancy and at the early years of their children's lives. By utilizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Studies among Chinese smokers have suggested that non-smoking wives have a limited influence on smoking cessation and report that smokers ignore their wives' interventions to make them stop smoking [20]. While the smokers accepted smoking restriction rules when their wives were pregnant [12], only a quarter quit smoking [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies among Chinese smokers have suggested that non-smoking wives have a limited influence on smoking cessation and report that smokers ignore their wives' interventions to make them stop smoking [20]. While the smokers accepted smoking restriction rules when their wives were pregnant [12], only a quarter quit smoking [21].…”
Section: Introductionmentioning
confidence: 99%
“…There have been very few studies in spousal social control in Asia. While a few qualitative studies have been conducted among Chinese smokers [12,37,38], to our knowledge, no other studies have been carried out in other Asian countries. The only Indonesian study by Nichter et al surveyed both husbands and wives of single-smoking couples about second-hand smoking exposure in their houses [23], however, social control was not the focus of the study.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in household settings, the space in which smoking fathers’ are allowed to smoke is often restricted due to considerations of morality and the desire to protect their child ( Oliffe et al, 2010 ), or a request from their wives ( Mao and Robinson, 2016 ). Spouses, specifically non-smoking ones, have been found to have a positive influence on smoking cessation.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, some studies conducted in China have shown how women managed to overcome the patriarchal barriers to exert their influence on smoking management at home, using their role as the health guardian of the family to this end ( Mao, 2013 , 2015 ; Mao and Robinson, 2016 ). They managed to restrict home smoking prior, during and after pregnancy ( Mao and Robinson, 2016 ), and joined forces with their mothers-in-law to gain more power at home ( Mao, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation